The Emergence of Modern Shi‘ism: Islamic Reform in Iraq and Iran by Zackery Heern (London: Oneworld Publications, 2015.) (American Journal of Islam and Society, 2017)
This is the first comprehensive work on the origins, development, and sociopoliticalramifications of the Usuli movement within Twelver Shi‘ism. Giventhat Wahid Bihbahani (1709-91), the founder and catalyst for Usuli revivalismduring the nineteenth century, is barely known in the West, it is a welcome additionto the growing Western literature on medieval and modern Shi‘ism. Thisongoing movement is the most powerful force in Twelver Shi‘ism.Using a wide range of primary and secondary sources, Heern highlightsthe emergence of modern Usulism during the eighteenth and nineteenth centuries.While locating its genesis within a global context, he outlines its ideologicalroots, historical background, and development. His central argument isthat Usulism was a response to the ummah’s changing sociopolitical conditionsand part of a wider trend of Islamic reform and revivalist movements that beganin the eighteenth century. He maintains that its emergence enabled the Shi‘iclerical establishment to attain sociopolitical and economic ascendancy in Iranand Iraq, and that the movement survived without government patronage bycultivating transnational links with the Shi‘i laity. For him, Shi‘i Islam’s recentascendancy is the result of the neo-Usuli movement ...